EFFICIENCY OF CULTIVATION OF POTATO VARIETIES OF DIFFERENT EARLY MATURITY IN THE CONDITIONS OF THE WEST KAZAKHSTAN REGION - Nurgaliyeva, G. K.; Mussina, М.; Nurgaliyev, А. М. (Ғылым және білім=Наука и образование=Science and education., 2021)
The importance of the variety has significantly increased in the context of the transition of crop production from chemical-technogenic farming systems based on comprehensive industrialization and chemization to adaptive (ecological-biosphere) systems aimed at preserving and increasing soil fertility and crop yields, based on the creation of sustainable agrobiocenoses that do not violate the natural processes occurring in the biosphere. It is believed that at the current rate of development of agriculture and breeding, the contribution of the variety to the further growth of potato productivity will continuously increase and reach 60-80%. In this regard, one of the most pressing problems in potato growing is the economic, biological and economic assessment of each variety cultivated in production. We have made an economic assessment according to three groups of indicators: all types of material and monetary costs (expenditure part); output of products in kind and value forms (income part); indicators of economic efficiency, which serve as the basis for an objective assessment of the advantages or disadvantages of a particular variety. The general indicators of economic efficiency are the net income per unit of planting area, the cost of a unit of production, and the level of profitability. The expenditure part includes labor costs with deductions, the cost of seeds, the cost of their preparation, fertilizers, plant protection products, the maintenance of fixed assets, including the cost of fuel, amortization, general economic expenses and other costs. Economic calculations have shown that the efficiency of potato cultivation largely depends on the variety. Значение сорта значительно возросло в условиях перехода растениеводства от химико-техногенных систем земледелия, базирующихся на всесторонней индустриализации и химизации, к адаптивным (эколого-биосферным) системам, направленным на сохранение и повышение плодородия почв и урожайности культур, на основе создания устойчивых агробиоценозов, не нарушающих естественных процессов, протекающих в биосфере. Считается, что при существующих темпах развития земледелия и селекции вклад сорта в дальнейший рост продуктивности картофеля будет непрерывно возрастать и достигнет 60 - 80%. В связи с этим одна из актуальных проблем в картофелеводстве - хозяйственно¬биологическая и экономическая оценка каждого сорта, возделываемого в производстве. Произведена экономическая оценка по трем группам показателей: все виды затрат материальных и денежных средств (расходная часть); выход продукции в натуральной и стоимостной формах (приходная часть); показатели экономической эффективности, которые служат основанием для объективной оценки достоинств или недостатков того или иного сорта. Обобщающими показателями экономической эффективности является чистый доход с единицы площади посадки, себестоимость единицы продукции, уровень рентабельности. Агротехнический прием, технология возделывания или система считаются
Keywords: научный журнал; отечественное издание; периодическое издание; журнал кксон; земледелие; растениеводство